2016
DOI: 10.1136/bmjopen-2016-011225
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of the benefits of group-based memory rehabilitation for people with neurological disabilities: implications for rehabilitation delivery and evaluation

Abstract: ObjectiveTo identify patient-perceived benefits of memory rehabilitation and draw transferrable lessons for the delivery and evaluation of similar interventions for people with neurological disabilities.MethodsA qualitative study was conducted as part of a pragmatic randomised controlled trial comparing 2 memory rehabilitation approaches with a self-help control group. Postintervention interviews were conducted with 20 participants with a diagnosis of traumatic brain injury, multiple sclerosis or stroke. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Instead, it is possible that the objective measures commonly used to assess performance in memory rehabilitation studies are not sensitive enough to capture the impact of memory training on patients’ everyday functioning. Previous studies on the impact of memory rehabilitation that incorporated a qualitative component have found that in the absence of improvement on quantitative measures, important gains were found in participants’ memory self-efficacy, memory knowledge, self-awareness of cognitive strengths and weaknesses, emotional adjustment, and compensatory strategy use (Chouliara & Lincoln, 2016). While the present study did not find any improvements on mental health and quality-of-life outcomes, it is apparent from the present review that measures of everyday impact are relatively neglected compared to measures of objective memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is possible that the objective measures commonly used to assess performance in memory rehabilitation studies are not sensitive enough to capture the impact of memory training on patients’ everyday functioning. Previous studies on the impact of memory rehabilitation that incorporated a qualitative component have found that in the absence of improvement on quantitative measures, important gains were found in participants’ memory self-efficacy, memory knowledge, self-awareness of cognitive strengths and weaknesses, emotional adjustment, and compensatory strategy use (Chouliara & Lincoln, 2016). While the present study did not find any improvements on mental health and quality-of-life outcomes, it is apparent from the present review that measures of everyday impact are relatively neglected compared to measures of objective memory.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson (2010) noted that the goal of rehabilitation should be to reduce the everyday impact of cognitive impairment and enhance overall well-being rather than focus on improving scores on cognitive tests. In line with this, there has been an increasing focus in several areas of intervention research on the utilization of participant-reported outcomes, such as self-reported memory or other measures of real-world impact (e.g., measures of overall well-being, such as mood, quality of life, or community participation), to assess intervention benefit (Chandler et al, 2016;Chouliara & Lincoln, 2016;Hudes et al, 2019;Price-Haywood et al, 2019;Salinas et al, 2016;Valentijn et al, 2005). Furthermore, it has been suggested that the inclusion of participant-reported measures may complement assessments of objective memory performance by providing a more complete picture of everyday functioning (Chouliara & Lincoln, 2016;Sherer & Sander, 2014).…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
“…The benefits of the holistic approach may not only lie in the potential improvements in daily functioning, but also community participation, productivity, self-efficacy and life satisfaction (Cicerone et al 2019 ; Nilsson et al 2011 ; Wilson 2013 ). Participant perspectives have revealed that knowledge and understanding of brain functions and the impact of ABI are beneficial aspects of holistic programs because they provide participants with information that reduces stress regarding current ability levels (Chouliara and Lincoln 2016 ; Nilsson et al 2011 ). Thus, it appears that improving self-awareness through education and feedback within the therapeutic setting while addressing the emotional, social, and behavioral consequences of ABI can promote improved functional outcomes in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…External memory aids are the dominant choice amongst persons with ABI and healthy adults (Evans et al 2003 ; Harris 1980 ; Intons-Peterson and Fournier 1986 ). Presumably, external compensatory strategies are favored in comparison with internal strategies or knowledge acquisition strategies for practical reasons because people are already familiar with them, it is perhaps simpler and quicker to train people to use them, and they may be easier to use in a variety of situations (Chouliara and Lincoln 2016 ; Zencius et al 1990 , 1991 ). One survey revealed that the four most commonly used external memory aids were calendars, wall charts, notebooks, and lists (Evans et al 2003 ).…”
Section: Compensatory Approachmentioning
confidence: 99%
“…Group‐based non‐pharmaceutical interventions are expected to promote success through social interaction [17,18] and have been applied in several disorders such as neuropsychiatric diseases including PD [19], traumatic brain injury [20], stroke [21], dementia [22], schizophrenia [23], depression [24], Huntington's disease [25] and multiple sclerosis [21]. Most of the group trainings are designed for cognitive rehabilitation or education since group‐based interventions in a community setting can promote communication amongst participants and encourage productive social engagement [18,26].…”
Section: Discussionmentioning
confidence: 99%